PENGARUH PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP TURNOVER KARYAWAN DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING PADA PT. TELKOM AKSES YOGYAKARTA - Ratri Meiliawati; Hery Sutanto; Yuni Siswanti (Jurnal Ilmu Manajemen, 2022)
This study aims to examine and analyze the direct effect of career development on employee turnover, the direct impact of compensation for employee turnover, the indirect effect of career development on employee turnover through employee engagement, and the indirect effect of compensation on employee turnover through employee engagement. The analytical tool used is Path Analysis descriptively using SPSS. The results are: (1) career development directly negatively and significantly influences employee turnover; (2) Compensation negatively and significantly influences employee turnover; (3) career development has an indirect negative and significant influence on employee turnover through employee engagement; (4) compensation has an indirect negative and significant influence on employee turnover through employee engagement. The company is advised to provide more access to information to all employees regarding fair promotion opportunities so that employee turnover can be further suppressed.